INNOVATION ASPECTS OF UKRAINE COMPETITIVENESS - N. Andreyuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Тhe basic indicators characterizing innovativeness of Ukrainian companies was analysed as well as the fact that the proportion of companies that have some development with the introduction of effective technologies that can produce the products according to the international standards, is insignificant. The factors, that prevented enterprises to innovate, were defined.